Characterization of the source(s) of lipocalin-2 mediating dietary obesity-induced hypertension. (10th June 2022) - Konja, D; Li, H; Fu, B; Singh, S; Wang, Y
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): This work was supported by the grants from the General Research Funds (17117017 and 17121714) and Collaborative Research Funds (C7037-17W) of Research Grant Council, the Areas of Excellence Scheme (AoE/M-707/18) of University Grants Committee Title: Characterization of the source(s) of lipocalin-2 mediating dietary obesity-induced hypertension. Introduction: Obesity upregulates lipocalin-2 (Lcn2), a pro-inflammatory adipokine, which in turn induces vascular and metabolic abnormalities. In mice, deletion of the Lcn2 alleles has protective effects against obesity-induced vascular and metabolic dysfunctions. Purpose: The present study investigated the sources of lipocalin-2 production as a mediator of dietary obesity-associated perivascular adipose tissue dysfunction and hypertension. Methods: The wild type (WT) littermates or mice with whole body knockout (LKO), adipose tissue (Adn-Cre)-, kidney (Wt1-Cre)-, liver (Alb-Cre)-, and granuloid cells (Lys-Cre)-selective deletion of the Lcn2 alleles were implanted with radio-telemetry transmitters at eight-weeks of age. Blood pressure was recorded at least four 12/12 light-dark cycles every four weeks for mice fed either standard chow (STC) or high fat diet (HFD). Wire myography was performed to evaluate the functional properties of mesenteric arteries, in the presence or absence of surrounding perivascular adipose tissues. Quantitative PCR, Western blotting as well as enzyme-linked immunosorbent assay (ELISA) were also performed to measure Lcn2 expression in tissues and blood respectively. Results: Compared to STC, HFD feeding increased systolic, diastolic, mean arterial and pulse pressure in WT mice. The amount of Lcn2 expressed in perivascular adipose tissues and present in blood were also higher in HFD-fed WT mice when compared to those fed with STC. Whole body deletion of Lcn2 alleles attenuated HFD- induced increase in blood pressure. Liver-selective deletion of Lcn2 alleles abolished the effect of HFD feeding on blood pressure, decreased Lcn2 expression in perivascular adipose tissues, and the concentration of Lcn2 in blood. Both whole body- and liver-specific deletion of Lcn2 alleles enhanced the anti-contractile activity of perivascular adipose tissues and abolished HFD-induced adipose tissue dysfunction. However, deletion of Lcn2 alleles selectively in adipose tissues, but not Wt1-Cre and Lys-Cre, partially mitigated the effects of HFD on perivascular adipose tissue function and blood pressure regulation. Conclusion: Lcn2 derived from different tissues are distinctively implicated in dietary obesity-induced perivascular adipose tissue dysfunction and hypertension.